Angular Elements: Bridging Frameworks with Reusable Web Components - Nikhil Kodali (International Journal of Intelligent Systems and Applications in Engineering, 2018)
Angular 6 introduced Angular Elements, a powerful feature that enables developers to create reusable web components using Angular. By leveraging the Web Components standard, Angular Elements allows Angular components to function as custom HTML elements that can be integrated into any web application, regardless of the underlying framework. This innovation enhances interoperability, simplifies the creation of dynamic and encapsulated UI components, and promotes a modular architecture. This paper explores the principles behind Angular Elements, its impact on web development, and how it streamlines development while improving the overall user experience.